Antecedents of employer's compliance with labour standards: a conceptual framework - Jaafar, Nur Afeza; Alias, Siti Noormi; Omar, Zoharah; Mustapa, Zainal Abidin (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
This paper aims to propose a conceptual model of employer’s compliance with labour standards in the Food and Beverage industry. The paper goes to analyse two factors that play a role in compliance behaviour. These factors are environmental and individual factors. Studies and surveys from the previous study were analysed and discussed in the context of factors that influence compliance. The factors were outlined in this paper by adopting Lindenberg’s Goal Framing Theory (GFT). The study will make a contribution to existing literature on employers’ compliance with labour standards. It is hoped that the finding may help the employers to better understand all related issues. The findings on the paper will include the type of factors that play a role in compliance behaviour and which factor appears to be the most influential to employers. It has to be noted here that it is important for employers to understand the importance of law compliance as it may be the factor that leads to company stability and productivity. It also will benefit the policy maker in encouraging employer towards labour standards practices, restructuring policies in labour standard and understanding the compliance trends of employers in future.